High-resolution in vivo imaging of bone and joints: a window to microarchitecture - Geusens, Piet; Chapurlat, Roland; Schett, Georg; Ghasem-Zadeh, Ali; Seeman, Ego; De Jong, Joost; Van Den Bergh, Joop (Nature Reviews Rheumatology, 2014)
Imaging is essential to the evaluation of bone and joint diseases, and the digital era has contributed to an exponential increase in the number of publications on noninvasive analytical techniques for the quantification of changes to bone and joints that occur in health and in disease. One such technique is high-resolution peripheral quantitative CT (HR-pQCT), which has introduced a new dimension in the imaging of bone and joints by providing images that are both 3D and at high resolution (82 ?m isotropic voxel size), with a low level of radiation exposure (3-5 ?Sv). HR-pQCT enables the analysis of cortical and trabecular properties separately and to apply micro-finite element analysis for calculating bone biomechanical competence in vivo at the distal sites of the skeleton (distal radius and distal tibia). Moreover, HR-pQCT makes possible the in vivo assessment of the spatial distribution, dimensions and delineation of cortical bone erosions, osteophytes, periarticular cortical and trabecular microarchitecture, and 3D joint-space volume of the finger joints and wrists. HR-pQCT is, therefore, a technique with a high potential for improving our understanding of bone and joint diseases at the microarchitectural level.
EVALuna2:12936